Rehabilitation through Reading: Evaluating Prisoners’ Right to Literacy as a Tool to Reduce Recidivism - Ade Adhari; Fransisca Iriani Roesmala Dewi; Anis Widyawati; Darius Andana Haris; Dwiky Chandra (Universitas Negeri Semarang, 2025)
Fulfilling inmates’ right to reading materials is crucial for effective rehabilitation within Indonesia’s correctional system, despite robust legal guarantees—from the 1945 Constitution to specific laws and regulations—practical implementation faces significant hurdles. High recidivism rates in Indonesia underscore the urgent need for genuine rehabilitation beyond mere punitive measures. Using a doctrinal legal research method, the analysis draws on statutory and conceptual approaches, supported by case studies from Class IIB Pinrang, LPKA Pekanbaru, and Class IIA Kupang. Findings highlight there is a persistent gap between legal mandates and on-the-ground reality. A fundamental shift is needed to bridge this: reading must be seen not just as a formal right, but as a core educational and rehabilitative tool for intellectual and personal development. Strategic improvements require stronger cross-sector collaboration, enhanced officer training, and outcome-based evaluation to ensure reading genuinely transforms inmates and supports their successful reintegration into society.